Supporting dataset for Compact and contactless reflectance confocal microscope for neurosurgery - Cui, J (University of Oxford, 2020)
Compact and contactless reflectance confocal microscope for neurosurgery Jiahe Cui, Raphael Turcotte, Karen Hampson, Matthew Wincott, Carla Schmidt, Nigel Emptage, Patra Charalampaki, and Martin Booth https://doi.org/10.1364/BOE.397832